PROTECTIVE ROLE OF PTEROSTILBENE ON PLASMA AND TISSUE GLYCOPROTEIN COMPONENTS IN HIGH-FAT DIET-FED AND STREPTOZOTOCIN-INDUCED TYPE 2 DIABETIC MICE - GUNASEELAN THANGASAMY; LEELAVINOTHAN PARI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the current study is to evaluate the effect of pterostilbene (PTS), on deranged plasma and tissue glycoprotein components in high-fat-diet (HFD) and streptozotocin (STZ)-induced type 2 diabetic mice. Methods: The experimental duration was 16 weeks. The C57BL6/J mice were fed a normal diet, normal diet with PTS, HFD, and STZ injection (10th week only), and diabetic mice with PTS for the past 6 weeks. Results: A significant increase in glycoprotein components such as hexose, hexosamine, fucose, and sialic acid (SA) in plasma was observed in diabetic mice. In hepatic and renal tissues, a significant decrease in SA with an increase in other glycoprotein components was detected in diabetic mice when compared with control mice. Oral administration of PTS significantly improved the glycoprotein levels in plasma and tissues of diabetic mice to near normal level. Conclusion: In this study, we resolved that PTS improves disturbed glycoprotein metabolism in HFD and STZ-induced type 2 diabetic mice.